The SLC26A9 inhibitor S9‐A13 provides no evidence for a role of SLC26A9 in airway chloride secretion but suggests a contribution to regulation of ASL pH and gastric proton secretion. Issue 11 (2nd October 2022) - Jo, Sungwoo; Centeio, Raquel; Park, Jinhong; Ousingsawat, Jiraporn; Jeon, Dong‐kyu; Talbi, Khaoula; Schreiber, Rainer; Ryu, Kunhi; Kahlenberg, Kristin; Somoza, Veronika; Delpiano, Livia; Gray, Michael A.; et al.
Abstract: The solute carrier 26 family member A9 (SLC26A9) is an epithelial anion transporter that is assumed to contribute to airway chloride secretion and surface hydration. Whether SLC26A9 or CFTR is responsible for airway Cl − transport under basal conditions is still unclear, due to the lack of a specific inhibitor for SLC26A9. In the present study, we report a novel potent and specific inhibitor for SLC26A9, identified by screening of a drug‐like molecule library and subsequent chemical modifications. The most potent compound S9‐A13 inhibited SLC26A9 with an IC50 of 90.9 ± 13.4 nM. S9‐A13 did not inhibit other members of the SLC26 family and had no effects on Cl − channels such as CFTR, TMEM16A, or VRAC. S9‐A13 inhibited SLC26A9 Cl − currents in cells that lack expression of CFTR. It also inhibited proton secretion by HGT‐1 human gastric cells. In contrast, S9‐A13 had minimal effects on ion transport in human airway epithelia and mouse trachea, despite clear expression of SLC26A9 in the apical membrane of ciliated cells. In both tissues, basal and stimulated Cl − secretion was due to CFTR, while acidification of airway surface liquid by S9‐A13 suggests a role of SLC26A9 for airway bicarbonate secretion.